Myths and Misconceptions on Covid-19: ‘Congo Check’ and ‘Talato’ Verification Experiences - Santos, Fabíola Ortiz dos (Frontiers in Communication, 2021)
Despite the challenges of connectivity and the digital divide that persists in Central Africa, an increasing number of citizens is engaging and interacting in social networks for fulfilling their informational needs. In these contexts, connected independent journalists act as gatekeepers linking the virtual and the physical offline spaces of the orality and mythical traditions of their societies. Myths are a way of making sense of reality and in times of crisis, lack of information truthfulness can open the gateways for uncertainties and disorientation. A more culture-centered approach to social media may provide an opportunity to halt misconceptions in these contexts serving as a corrective mechanism against false information. This paper asks: How do fact-checkers combat/halt Covid-19 myths and misconceptions in the Democratic Republic of Congo and Central African Republic? How do they engage in social media networks towards sense-giving and sharing corrective information? It discusses two cases of online media projects, ‘Congo Check’ and ‘Talato’, led by independent journalists that combine fact-checking skills when communicating the pandemic and attempt to engage civil society to better consume information. The data collection comprises of interviews with the journalists, as well as the Twitter handling of these projects. This study sheds light to how independent voluntary initiatives can foster the correction of Covid-19 myths and misconceptions in their localities.